An Investigation of Justice in supply chain relationships and their performance impact - Narasimhan, Ram; Narayanan, Sriram; Srinivasan, Ravi (Journal of Operations Management, 2013)
AbstractJustice is important in improving performance of supply chain relationships. However, the role of justice in improving performance in supply chain relationships is an under‐investigated subject in the literature. In studying the joint impact of justice dimensions, the traditional assumption is that the three forms of justice interact with each other in a multiplicative manner. However, this assumption creates a managerial problem as discussed in this paper. We outline a different view of how the justice dimensions interact with one another utilizing the constraining factor model (CFM). We show that the CFM resolves some of the problems arising from the choice of multiplicative interaction of justice measures on performance. Specifically, we demonstrate that an increase in procedural, distributive or interactional justice results in a significant and positive improvement in performance only if the specific justice dimension is the constraining factor in the relationship. Overall, our analysis suggests that all three dimensions are important and a high level of one of the justice elements will not compensate for a low level of another, a view that is put forward by a number of past research studies in justice. We discuss the theoretical and managerial implications of our findings.